Titik Temu Agama-agama dalam Analisis Interpretatif - Kunawi, Kunawi (Program Studi Studi Agama-Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2012)
The discourses about religion will never come to end. Religion will always be a topic of public sphere and cannot be separated from subjective views. Religion carries the important aspect from which it functions as a vehicle for human being to act of how runs our life in this world. This condition tends to convey religion into an exclusive side. On the one hand, for its adherents, religion (faith) is a basic principle that funnels them to achieve the mean of their life. On the other hand, religion also guide its adherents how to interact with their surroundings politically, economically, socially and religiously. It means that religion is operational and functional doctrine. In social life, religion is used to have such condition where all the structure is well constructed. Basically, the “big religions” (Judaism, Christianity and Islam) are from the same derivation: Semitic. Tauhid is one example of that derivation, besides universal values which inherently arise from those religions. From this point of view, we can say that religion actually has already brought such linear characters among one and another. In this regard, this article attempts to portray the convergences of those religions by using the method of interpretative analysis